2012
DOI: 10.1111/jpn.12024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ensiling moist field bean (Vicia faba), pea (Pisum sativum) and lupine (Lupinus spp.) grains on the contents of alkaloids, oligosaccharides and tannins

Abstract: Ensiling legume grain may be an inexpensive and ecologically interesting method to produce a high-protein feed of local origin. The typically patchy maturation recommends harvesting and ensiling the seeds in moist condition. Developing a method for preserving legume grains harvested before maturation by lactic acid fermentation would have several advantages. Under laboratory conditions, crushed legume seeds of beans, peas and lupines with high moisture content of 35 % were ensiled with different additives (mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…Gefrom et al. () have studied the effect of ensiling on the concentration of QAs in crushed lupin seeds. A sweet (Bora) and a bitter (Azuro) cultivar of L. angustifolius were harvested at 65% dry matter content and four different kinds of model silages were prepared.…”
Section: Assessmentmentioning
confidence: 99%
“…Gefrom et al. () have studied the effect of ensiling on the concentration of QAs in crushed lupin seeds. A sweet (Bora) and a bitter (Azuro) cultivar of L. angustifolius were harvested at 65% dry matter content and four different kinds of model silages were prepared.…”
Section: Assessmentmentioning
confidence: 99%
“…grains on the contents of alkaloids, oligosaccharides and tannins was studied by Gefrom et al (2013). As an overall effect, lactic acid fermentation reduced the content of tannins and oligosaccharides.…”
Section: Anti-nutritional Substancesmentioning
confidence: 99%
“…For example, ensiling Cotswold Common, Reznos, and Teruel sainfoin ( Onobrychis viciifolia ) resulted in a reduction of extractable tannins compared to fresh plant material [Lorenz et al, ]. Alipour and Rouzbehan [] and Gefrom et al [] also found that the ensiling process reduced tannins in ensiled legume grain and grape pomace. The reduction in tannins during ensiling seems to be a function of chopping, storage time, and anaerobic conditions possibly as a result of enzymatic and/or oxidative reactions [Makkar and Singh, ; Ben Salem et al, ; Alipour and Rouzbehan, ].…”
Section: Discussionmentioning
confidence: 99%